2003
DOI: 10.3171/jns.2003.98.2.0291
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intrathecal baclofen therapy for severe spasticity of cerebral origin

Abstract: Intrathecal baclofen provides effective long-term treatment of spasticity of cerebral origin and its effects do not appear to diminish with time. This therapy is frequently associated with adverse side effects that usually can be alleviated by adjustments in dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
106
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(119 citation statements)
references
References 12 publications
6
106
3
4
Order By: Relevance
“…[1][2][3] The dose of ITB therapy has shown to increase during the first 12-18 months of therapy, very likely due to optimization of the individual needed dose, after which it stabilizes. 2,4,5 However, unexplained dose increases may still occur in up to 20% of ITB patients after these first 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The dose of ITB therapy has shown to increase during the first 12-18 months of therapy, very likely due to optimization of the individual needed dose, after which it stabilizes. 2,4,5 However, unexplained dose increases may still occur in up to 20% of ITB patients after these first 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…The stroke consensus panel reported that a reasonable time to achieve optimal dosing was 3 months, with longer periods required in some individuals (16,23). Albright et al (24) observed decreased tone up to 5 years out, with stable dosing occurring after the first 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…17 The only outcome addressed in our study is survival; other benefits of ITB therapy have been previously reported and include tone reduction, comfort, ease of care, and decrease in number of anticipated orthopedic procedures. 3,5,[24][25][26][27] The most obvious limitation of the present study was that the cohorts were not prospectively randomly assigned. However, blinding of observation would not be relevant with the outcome measure of survival, and implementation of a randomly assigned study would be impossible in current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal baclofen (ITB), which was approved by the US Food and Drug Administration in 1996 for use in individuals with CP, is effective in the reduction of spasticity as well as dystonia and is frequently used to treat hypertonicity associated with CP. [2][3][4] In addition to the long-term reduction of hypertonicity, authors have reported improvement in comfort, positioning, ease of care provision, and motor function in select groups of individuals, and a reduction in the anticipated need for orthopedic surgery. 2,5,6 Progression of hip dislocation may be reduced with ITB, although the effect of ITB on the progression of scoliosis is controversial.…”
mentioning
confidence: 99%